DESARROLLO TERRITORIAL: UNA APROXIMACIÓN A SU PROBLEMÁTICA - Sheput Moore, Juan Manuel (2022)
It is common to hear that decentralization and regionalization have failed in Peru. However, beyond general statements such as blaming decentralization for inefficiency and corruption, there is no in-depth analysis that uncovers the true regional problems. What happens is that there are no entities, not from academy, political parties or think tanks, that have approached the subject seriously and in depth, taking into account the complexity of regionalization, the way in which public policies that compromise it or how regionalization would help to build a vision of the future. This article is an introduction to it.